Development and characterisation of a cold molecule source and ion trap for studying cold ion-molecule chemistry - Steer, E (2016)
A novel apparatus, combining buffer-gas cooling, electrostatic velocity selection and ion trapping, has been constructed and characterised. This apparatus is designed to investigate cold ion-molecule chemistry in the laboratory, at a variable translational and internal (rotational) temperature. This improves on previous experiments with translationally cold but rotationally hot molecule sources. The ability to vary the rotational temperature of cold molecules will allow for the experimental investigation of post-Langevin capture theories.